2019
DOI: 10.1136/bmjopen-2018-022186
|View full text |Cite
|
Sign up to set email alerts
|

Integrating community health workers into the formal health system to improve performance: a qualitative study on the role of on-site supervision in the South African programme

Abstract: ObjectivesTo explore the role of on-site supervision in community health worker (CHW) programmes and CHW integration into the health system. We compared the functioning of CHW teams reporting to a clinic-based nurse with teams supervised by a community-based nurse. We also consider whether a junior nurse can provide adequate supervision, given the shortage of senior nurses.DesignA case study approach to study six CHW teams with different configurations of supervision and location. We used a range of qualitativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
101
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(106 citation statements)
references
References 25 publications
5
101
0
Order By: Relevance
“…On the whole, PHC facility staff and middle managers at subdistrict and district levels did not have much of a role in supporting and overseeing the work of the WBOTs. This resonates with previously documented problematic relationships between CHWs and the PHC system, poor organisational support in PHC facilities and a prevalent perception of not being respected 1 16 22 23 27. While the immediate supervisor of the CHWs is the TL, the PHC facility managers and staff have a pivotal role in supporting, overseeing and integrating the work of the WBOTs.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…On the whole, PHC facility staff and middle managers at subdistrict and district levels did not have much of a role in supporting and overseeing the work of the WBOTs. This resonates with previously documented problematic relationships between CHWs and the PHC system, poor organisational support in PHC facilities and a prevalent perception of not being respected 1 16 22 23 27. While the immediate supervisor of the CHWs is the TL, the PHC facility managers and staff have a pivotal role in supporting, overseeing and integrating the work of the WBOTs.…”
Section: Discussionsupporting
confidence: 74%
“…Yet the evidence from this study shows that approached holistically, supportive supervision involves a wide range of actors and relationships within a system 9. There is considerable evidence, from both the NW and elsewhere, that CHWs/WBOTs are often treated as outsiders by actors in the PHC system and perceive themselves as exploited and unacknowledged by the broader system 16 22–25. On the other hand, respondents were almost unanimous on the importance of the WBOT programme for communities.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Another study aiming to profile current CHWs based in KZN [20] identified poor communication between them and facility-based nurses in the referral of clients, leading to poor job satisfaction among CHWs and an understanding of ongoing health services provided to clients. A study [21] to explore the role of on-site supervision of CHWs in South Africa found that those supervised by senior nurses were more motivated and performed a greater range of tasks, and those that were clinic-based were better integrated in the health system and therefore more able to ensure continuity of care. In contrast, teams supervised by junior supervisors, or based in the community, had less engagement with clinic staff, and were less able to ensure necessary care for patients, resulting in lower levels of trust from clients.…”
Section: Discussionmentioning
confidence: 99%